The extent of influence of O–D matrix on the results of public transport modeling - Ušpalytė-Vitkūnienė, Rasa; Grigonis, Vytautas; Paliulis, Gražvydas (Transport, 2012)
A rapidly developing and equality-based society needs a reliable and attractive public transport system. With booming mobility in Lithuania, a great importance has been attached to the sustainable development concept, and public transport has been given priority in the urban transport system. Accessibility and comfort of public transport are essential indicators that guarantee equal travelling opportunities for all people. Transport modelling is the only economical and sufficiently reliable way to carry out a forward assessment of the impact of innovations to be applied to the overall system without involvement of passengers. This paper considers estimation of the origin–destination (O–D) matrix and its size correction. The public transport (PT) system of Vilnius City was taken as a basis for the research. Modelling of Vilnius City public transport was carried out with the help of VISUM software. Modelling of the public transport route network in Vilnius is aimed at improving the quality of life of inhabitants of the city. The O–D matrix is one of the key elements in modelling. Reliability of modelling results is based on reliability and size of the matrix. Although many scientists analyse the problem of estimating an O–D matrix, this paper focuses on the size of the O–D matrix required in order to give reliable results in PT modelling. During the first step, the matrix of 230 transport districts is estimated, which is reduced by 10 percent with every following step. The aim of this article is to find the break point in the size of O–D matrix where the reliability of PT modeling results falls. First Published Online: 26 Jun 2012